HOW TO CORRECTLY IDENTIFY HERBAL MATERIALS IN MARKET? A CASE STUDY BASED ON DNA BARCODES - Zhang, Dequan; Yang, Yongshou; Jiang, Bei; Duan, Lizhen; Zhou, Nong (African Journal of Traditional, Complementary and Alternative Medicines, 2014)
Background: Traditional methods for identifying herbal medicines have many shortcomings. In this study, we aim to test discriminating ability of DNA barcodes and explore feasible method on evaluating identification results. Materials and Methods: Materials of whole-plant medicines were sampled from herbal market. 111 samples were used for DNA sequencing of ITS2 and trnH-psbA regions. Assembled sequences were searched against reference database using the BLAST method. Comprehensive evaluation based on pharmacognostic investigation, macroscopic identification and identification of DNA barcodes were performed for authentication of the herbal materials. Results: As a result, ITS2 had better identifying power than trnH-psbA in species-specific level (55.86% & 45.95%), as well as worse success rate of DNA sequencing (74.58% & 94.59%). In total, 89.19% individuals could be identified in genus level at least. Conclusion: It was revealed that DNA barcoding was useful tool in identifying herbal materials. Both ITS2 and trnH-psbA should be incorporated into the standard regions of DNA barcodes for identifying herbal materials.